Synthesis and characterization of lead Zirconate Titanate (Pb[Zr0.52Ti0.48]O3) properties via high energy planetary ball milling - Nur Shafiza Afzan, Sharif (2015)
Pb(Zr0.52Ti0.48)O3 piezoelectric was successfully prepared by solid state reaction method via high energy planetary ball milling. This method which implements a single firing step where the calcinations process has been skipped thus successfully controls the higher evaporation amount of PbO during sintering process. Optimization is important on sintering parameters when using a single firing process. With the optimum processing parameters and sintering conditions (temperature and duration), the excellent PZT formation and optimum electrical properties of PZT ceramics was produce. The properties of piezoelectric materials were modified by different milling duration (20, 40 and 60 hours) and sintering parameters (temperature: 1000, 1050, 1100, 1150 and 1200 °C; soaking time: 1, 2 and 3 hours). Based on the study, sample milled for 40 hours show suitable milling duration with SEM analysis promotes fine particles and densification, thus achieved an excellent dielectric and piezoelectric properties. Preliminary works have been done in order to find suitable sintering temperature and durations to obtain the best PZT formation with good piezoelectric properties. This study continued to the next phase with 40 hours and sintered at different sintering temperatures (1050, 1100, 1150 and 1200 °C) and durations (1, 2 and 3 hours). According to the results, XRD analysis indicate that samples sintered at different sintering temperature and duration show single perovskite phase and no crystal structure changes were detected. However, sample sintered at 1200 °C for longer sintering duration (3 hours), new phase which mainly of excess PbO oxides were identified. SEM analysis was carried out and shows that, fine and dense grain sizes were achieved after sintering at 1050, 1100 °C for 1 hour. Increasing the sintering temperature and duration, larger and irregular grain size were observed. SEM observation indicated that sample sintered at 1200 °C for 2 hours durations shows better grain morphology whereby homogenous and dense microstructure were obtained. Increasing of the sintering temperature and durations, produces an increase of the grain size, increase in dielectric and piezoelectric properties thus decrease the value of dielectric loss for PZT ceramic. However, higher sintering temperature (1200 °C) and longer sintering durations (3 hours), the relative density slightly decreases to about 92 % of the theoretical density and causes the electrical properties to decrease. This phenomenon happens due to the evaporation of PbO whereby the existence of PbO phase was detected in the XRD patterns. Based on the results, sample sintered at 1200 °C for 2 hours show optimum sintering parameter and exhibits excellent room temperature electrical properties, which are listed as follows: εr = 2400, tan δ = 0.009, d33 = 256 pC/N, kt = 0.48, kp = 0.42 and Qm = 1716